Neurofilament light chain levels indicate acute axonal damage under bortezomib treatment - Cebulla, Nadine; Schirmer, Daniel; Runau, Eva; Flamm, Leon; Gommersbach, Sonja; Stengel, Helena; Zhou, Xiang; Einsele, Hermann; Reinhold, Ann-Kristin; Von Bieberstein, Bruno Rogalla; Zeller, Daniel; Rittner, Heike; et al. (Journal of Neurology, 2023)
Introduction: Bortezomib (BTZ) is a selective and reversible proteasome inhibitor and first line treatment for multiple myeloma (MM). One of the side effects is BTZ-induced peripheral neuropathy (BIPN). Until now there is no biomarker which can predict this side effect and its severity. Neurofilament light chain (NfL) is a neuron specific cytoskeletal protein, of which higher levels can be detected in peripheral blood in case of axon damage. In this study, we aimed to evaluate the relationship between NfL serum levels and characteristics of BIPN. Methods: We performed a first interim analysis of a monocentric, non-randomized, observational clinical trial including 70 patients (DRKS00025422) diagnosed with MM in the inclusion period of June 2021 until March 2022. Two groups of patients—one with ongoing BTZ treatment at the time of recruiting, and one with BTZ treatment in the past—were compared to controls. NfL in serum was analyzed via the ELLA™ device. Results: Both patients with previous and ongoing BTZ treatment had higher serum NfL levels than controls, and patients with ongoing BTZ treatment had higher NfL levels than patients with BTZ treatment in the past. Serum NfL levels correlated with electrophysiological measures of axonal damage in the group with ongoing BTZ treatment. Conclusion: Elevated NfL levels indicate acute axonal damage under BTZ in MM patients.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Bortezomib; Bortezomib-induced peripheral neuropathy; Multiple myeloma; Nerve conduction studies; Neurofilament light chain; Peripheral neuropathy